ANALISIS MANAJEMEN KEUANGAN RUMAH TANGGA DAN KEUANGAN NEGARA DAMPAK PANDEMI COVID-19 MENURUT PERSPEKTIF EKONOMI SYARIAH - Rika Yuliastuti (STIE Mahardhika, 2022)
The research’s title is An Analysis of Household Financial Management and State Finances During the Covid-19 Pandemic According to the Sharia Economic Perspective. The background of this research is the condition of the outbreak of the COVID-19 pandemic in all countries in 2020. The move to close the economic sector has an impact on household finances and state finances. The purpose of this study is to analyze household financial management and state finances during the COVID-19 pandemic from a sharia economic perspective. The method used in this study is a descriptive qualitative method approach using content analysis techniques. From a study conducted on various literatures, the following points are shown. First, should follow the example of the Prophet in managing family financial spending by using the principles of a simple lifestyle. When managing shopping, prioritize needs, not wants. Second, the expenditure should be regulated based on the amount of income. When an epidemic occurs which results in reduced income, some spending must be cut. Third, keep spending your wealth on infaq, shodaqoh etc when you are free or when you are short of sustenance. Fourth, set the largest allocation for mass basic needs. As for the regulation of state finances according to the sharia economy in an epidemic condition, all income owned by the state is allocated to meet the basic needs of the people. Especially the basic needs of each household and the fulfillment of health needs. In the Islamic economic system, there is a solution to rearrange regulations on macro and micro economic aspects to become sharia-based.